2022
DOI: 10.1371/journal.pone.0272255
|View full text |Cite
|
Sign up to set email alerts
|

The evolution and co-evolution of a primary care cancer research network: From academic social connection to research collaboration

Abstract: Academic networks are expected to enhance scientific collaboration and thereby increase research outputs. However, little is known about whether and how the initial steps of getting to know other researchers translates into effective collaborations. In this paper, we investigate the evolution and co-evolution of an academic social network and a collaborative research network (using co-authorship as a proxy measure of the latter), and simultaneously examine the effect of individual researcher characteristics (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In contrast with the assumed advantages of collaboration and high-quality research demands, research collaboration does not happen automatically; this is also the case in HPE research (Stadler et al, 2019). Many studies on research collaboration, often using social network approaches to show co-authorship practices (Kezar, 2005;Kyvik & Reymert, 2017;Vermond et al, 2022), have indicated that research collaboration only happens under certain conditions. Besides, HPE research asks for interdisciplinary collaboration, which is often even more challenging because researchers must bridge boundaries between disciplinary paradigms (Mäkinen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with the assumed advantages of collaboration and high-quality research demands, research collaboration does not happen automatically; this is also the case in HPE research (Stadler et al, 2019). Many studies on research collaboration, often using social network approaches to show co-authorship practices (Kezar, 2005;Kyvik & Reymert, 2017;Vermond et al, 2022), have indicated that research collaboration only happens under certain conditions. Besides, HPE research asks for interdisciplinary collaboration, which is often even more challenging because researchers must bridge boundaries between disciplinary paradigms (Mäkinen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with the assumed advantages of collaboration and high-quality research demands, research collaboration does not happen automatically; this is also the case in HPE research (Stadler et al, 2019). Many studies on research collaboration, often using social network approaches to show co-authorship practices (Kezar, 2005; Kyvik & Reymert, 2017; Vermond et al, 2022), have indicated that research collaboration only happens under certain conditions. Besides, HPE research asks for interdisciplinary collaboration, which is often even more challenging because researchers must bridge boundaries between disciplinary paradigms (Mäkinen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%